Thermal imaging of concrete dam surfaces to support the control of the evolution of pathologies - Henriques, M. J. (2015)
The pathologies of structures that cause changes of surface temperatures can be detected by the analysis of the temperature of walls and other surfaces. The measurement of the surface temperatures can be easily performed with the use of thermal imaging cameras which work like an ordinary digital camera and give, instantly, a colour image where the colours are related with the temperature of the surface. This paper presents a study of the use of this methodology in the monitoring of concrete dams, specifically on the detection of resurgences of water on the downstream face, usually related with the transfer of water. Three concrete arch dams were used to test this methodology: Alto Ceira, Cabril and Alto Ceira II. On the day on which the images were taken (4th of June of 2013), Alto Ceira and Cabril were under normal operation. Both structures presented important cracks. These dams were used to test if, under normal conditions, namely with the thermal camera more than 100 m away from the dam, it was possible to detect colder areas. Alto Ceira II was, at that day, near the end of the construction. As it has several thermometers inside the concrete, the temperatures measured by these were used to validate the information on the thermal images.